Integrasi Permainan Tradisional Curik-Curik dalam Model Teams Games Tournament Pada Pembelajaran IPAS - Putu Rian Indrawan; Gusti Ngurah Arya Yudaparmita; Kadek Hengki Primayana (Alpatih Harapan Semesta, 2026)
Contemporary elementary education emphasizes student-centered, culturally responsive, and engaging instructional approaches. In this context, integrating the traditional Indonesian game Curik-Curik into the Teams Games Tournament (TGT) model for teaching Natural and Social Sciences (IPAS) in Grade 4 offers a promising pedagogical strategy. This study aims to explore the relevance, potential, and empirical foundation of this integration through a qualitative descriptive literature review. Relevant scholarly peer-reviewed studies featured in nationally recognized academic periodicals between 2020 and 2025 were analyzed. Findings indicate that the TGT model effectively enhances students’ learning motivation and conceptual understanding in IPAS, particularly at the Grade 4 level. Furthermore, traditional games like Curik-Curik demonstrate strong pedagogical value as contextual learning tools that foster cognitive development and social values such as cooperation, strategy, and sportsmanship. Importantly, empirical studies confirm that combining TGT with traditional games creates an active, meaningful, and culturally grounded learning experience. Thus, integrating Curik-Curik into the TGT framework demonstrates robust conceptual foundations alongside empirical applicability, thereby supporting the objectives of the Merdeka Curriculum and fostering the Pancasila Student Profile. Profiles that honor local cultural diversity.